Working out an Innovative Strategy for the Development of the Oil & Gas Complex in the Context of Global Energy Development and the Entrance of the Russian Federation to the World Trade Organization - V Yu Preys (RUDN Journal of Economics, 2014)
The present paper determines the conceptual conditions for enhancing the efficiency of the Oil & Gas complex functioning, the conditions connected with the launching of the Customs Union and the entrance of the Russian Federation to the World Trade Organization. The author points out that there is a need to develop a new approach to the problem of strategic bases for the functioning and innovative development of the oil & gas complex in the light of the implementation of the innovative strategy for the development of Russia, the launching of the Customs Union and the entrance of the Russian Federation to the World Trade Organization. Besides, the present research substantiates the necessity of working out an innovative strategy for the development of the Oil & Gas sector taking into consideration new demands of the Strategy “Innovative Russia 2020”.